Pengembangan Modul Berbasis Kearifan Lokal "Nyadran" di Kabupaten Lamongan Tema 3 Subtema 1 Kelas V SD Negeri Pangkatrejo - Pistanty, Mingle A; Sarima, Sarima; Ashari, Makmum (Widyagogik, 2024)
The integration of science learning through experimental activities is crucial in enhancing students' understanding of natural product chemistry. This study explores the antioxidant potential of Centella asiatica (Gotu kola) extract as a contextual learning medium in scientific education. Centella asiatica is a medicinal plant widely used in traditional medicine for its bioactive compounds, including triterpenoids, flavonoids, alkaloids, and saponins, which exhibit significant antioxidant properties. This study aims to evaluate and compare the antioxidant activity of C. asiatica extracts obtained using three different solvents: 70% ethanol, N-hexane, and ethyl acetate, utilizing the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Antioxidant activity was assessed based on the ability of the extract to scavenge DPPH radicals, measured spectrophotometrically at a wavelength of 517 nm. The findings revealed that all extracts exhibited antioxidant activity, with the 70% ethanol extract demonstrating the highest potency, achieving an IC50 value of 19.50 µg/ml, compared to N-hexane and ethyl acetate extracts. These results highlight the potential of C. asiatica as a natural antioxidant source, relevant for health product development and scientific experimentation in educational settings. This study underscores the importance of incorporating laboratory-based research into science curricula to enhance students' analytical and experimental skills while fostering an appreciation for the application of natural product research in health sciences.